Cytokines and tuberculosis : an investigation of tuberculous lung tissue and a comparison with sarcoidosis - Bezuidenhout, Juanita (University of Stellenbosch. Faculty of Health Sciences. Dept. of Biomedical Sciences., 2008)
Thesis (PhD (Pathology. Anatgomical Pathology))--University of Stellenbosch, 2005.